The effect of aspirin therapy on the increasing of Barthel Index score in stroke patients - Alifiar, Ilham; Kamal, Hilda Fitria; Sukmawan, Yedy Purwandy (Pharmacy Reports, 2021)
Stroke, a disorder of nervous system function, is caused by impaired blood circulation to the brain. Post-stroke patients often receive aspirin therapy, yet many still require assistance from others for daily activities. This study aimed to evaluate the impact of aspirin therapy on functional improvement in stroke patients at RSUD Dr. Soekardjo Tasikmalaya, using the Barthel Index score as a measure of patients' ability to perform activities of daily living. A retrospective, descriptive observational approach was employed, analyzing data from stroke patients who underwent aspirin therapy between February and May 2019. The study assessed patients' functional status before and after aspirin therapy, focusing on the level of dependence. Pre-test results indicated that 80.97% of patients fell within the mild dependence category, while 19.03% were classified as moderately dependent. After undergoing aspirin therapy, post-test results revealed a substantial improvement in patients’ functional status. Only 4.76% of patients remained in the moderate dependence category, while a remarkable 95.24% transitioned to the independent range. These findings suggest that aspirin therapy may play a crucial role in enhancing the functional recovery of stroke patients, potentially promoting a higher level of independence and improved quality of life.